Management Principle of Lake Toba Tourism Destination: Local People's Perception - Jhonson Pardosi; Nur Cahaya Bangun; Ilham Mirzaya Putra (Journal of Indonesian Tourism and Development Studies, 2021)
In tourism development, community participation is very important. Community participation does not just appear but must start from the correct perception of tourism. The local community, with all their perceptions about tourism management, have already been involved in tourism management. The aim of the research is: 1) to find out the local peopleâ€™s perception to the principal tourism destination management 2) to find out the model of sustainable tourism development in Simanindo District, Samosir Regency. The type of research is social survey and descriptive-quantitative. The technique used in sampling is the Franc Lynch method, with a sample of 95 people as respondents, aged 15-64 years was obtained. The data type used represents primary by using a questionnaire with a Likert scale in each question. Data analysis techniques were using value perception and multiple regression analysis. The result from this research showed: 1) The percentage of the average value of the independent variable is 85%, this means that the perception of the local community on the principles of managing Lake Toba tourist destinations are in positive or good areas 2) Sustainable tourism development has a positive relationship and is influenced simultaneously by service, attraction, human resources, environment, and participation. Therefore, the model of sustainable tourism development should be stressed on the attraction and the human resource in the Simanindo District.Â  Keywords: Community tourism development, sustainable community, sustainable tourism.